Melissopalynology of Coffea arabica honey produced by the stingless bee Tetragonisca angustula (Latreille, 1811) from Alajuela, Costa Rica - Enrique Moreno; Patricia Vit; Ingrid Aguilar; Ortrud M. Barth (AIMS Agriculture and Food, 2023)
Tetragonisca angustula is the most widespread stingless bee species, from Mexico to Northern Argentina. It is called Mariola in Costa Rica. Native plant species offering food resources and nesting sites to stingless bees are included in reforestation and conservation programs. In Costa Rica there are continuous initiatives on listing flora supporting meliponiculture. In this study, a sample of pot-honey was collected from sealed honey pots within nests of Tetragonisca angustula in Alajuela, Costa Rica. It was acetolyzed following standard methods and the pollen types were visualized by microscopic analysis at 200X magnification using a Nikon Eclipse Ni binocular scope. Electronic brightfield micro-photographs were obtained at 1000X magnification and pollen types were plated. Palynological descriptions were provided for major pollen grains. The botanical identifications of plant families and genera were established by comparison with pollen atlases and were validated consulting the 2022 Tropicos Missouri Botanical Garden database. Seventy-nine pollen types were recognized in the pollen spectrum, representing 36 families and 67 genera of flowering plants. Their habits were trees (51%), lianas/vine (11%), herbs (19%), herb/tree (5%), shrubs (5%), shrub/tree (1%) and not assigned (8%). This assemblage indicated the presence of lowland tropical forest elements, probably small relicts of secondary forest surrounding open and cultivated areas where Coffea arabica pollen dominated in the honey pollen spectrum with 54.3% of total counts, with secondary Paullinia sp. 8.7%, Vochysia sp. 4.8% and Cassia sp. 4.2% and 95% of pollen taxa present in < 3% relative frequency. Taxa offering only pollen (polleniferous) were considered honey contaminants (32%) not explaining the nectar botanical origin of honey.